Strategi Adaptasi Masyarakat Terhadap Perubahan Iklim Di Kecamatan Sungai Batang Kabupaten Indragiri Hilir - Afrizal Afrizal; Mubarak Mubarak; Imam Suprayogi (Pelantar Press, 2023)
Climate change clearly affects conditions in an environment or region, whether it is an increase in disaster events or other aspects such as the economic, social and ecological aspects of the affected area. This research can provide information on rainfall conditions in Sungai Batang sub-district from monthly to yearly, this rainfall information can also provide information on trends that occur from year to year, this trend information can identify how climate change is occurring in Sungai Batang sub-district and the impact of how climate change adaptation strategies need to be carried out. Based on the SWOT analysis, the climate change adaptation strategy chosen for quadrant III is the W-O (Weakness – Opportunities) strategy. This strategy combines internal factors, namely weaknesses, with external factors, namely opportunities. The W-O strategy aims to take advantage of existing opportunities while minimizing the weaknesses they have.